Turi leaf extract Ag nanoparticle liquid soap (Review of physical properties and antibacterial activity) - Amananti, Wilda; Budi Riyanta, Aldi (Universitas Ahmad Dahlan, 2024)
Research has been carried out on manufacturing liquid soap silver nanoparticles of Turi leaf extract. Ag nanoparticles have been used in various cosmetic and personal care products. This is because Ag nanoparticles have potential advantages such as increasing product stability, increasing absorption, and the ability to give special effects to the skin. From the physical properties test results, all soap formulas meet the standards set based on organoleptic, physical properties, pH, density, and viscosity. This research discusses the antibacterial activity of liquid soap. Formula 1 showed better antibacterial activity than formulas 2 and 3, with an inhibitory area reaching 23.84 mm. This can be explained by the fact that Formula 1 has a smaller particle size, namely 2161 nm. Formula 1 has the lowest AgNO3 concentration. The higher the concentration of AgNO3 used in the synthesis, the greater the amount of Ag+ that must be reduced, resulting in greater agglomeration and a larger size distribution of Ag nanoparticles.